The Comparison of Boarding School Student’s Capability in Solving HOTS Question of Islamic History Subject - Muthia Franika Anggita Pratiwi; Eka Rizki Amalia (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This research was conducted to determine the ability and the comparison to solve HOTS questions of Islamic History subject of the 11th grades of MAN I and MAN II Surakarta boarding school. The research applied a comparative quantitative method by comparing the ability to solve HOTS questions of Islamic History subject of the 11th grade of MAN I and MAN II Surakarta students. The result reveals that MAN I students’ ability to solve HOTS questions reaches 22% and is categorized as low, 55% of students obtained scores of medium category, and 23% of students are in the high category. Meanwhile, for MAN II students, 14% obtained scores for the low category, 49% for the medium category, and 37% for the high category. There were no significant differences related to the ability to solve HOTS questions of Islamic history of both schools. With HOTS’s evaluation, the students can expand the ability to solve HOTS questions, and the teachers can take into consideration to implement HOTS’s evaluation.